55.0k views
1 vote
Solve for x. Enter the solutions from least to greatest.Round to two decimal places.(x+3)^2 – 3 = 0lesser x =greater x =

1 Answer

0 votes

The given equation is


\mleft(x+3\mright)^2-3=0

Simplify the equation by adding 3 to both sides of the equation


\mleft(x+3\mright)^2-3+3=3

This is simplified to give


\mleft(x+3\mright)^2=3

This can be further simplified as follows


\begin{gathered} x+3=\pm\sqrt[]{3} \\ x=\pm\sqrt[]{3}-3 \end{gathered}

Hence, the solution is


\begin{gathered} x=-\sqrt[]{3}-3,x=\sqrt[]{3}-3 \\ \Rightarrow x=-1.73-3,x=1.73-3 \\ x=-4.73,x=1.27 \end{gathered}

Therefore, the solution is

Lesser x = - 4.73

Greater x = 1.27

User Mfadel
by
4.4k points